2005
DOI: 10.1042/bst0331502
|View full text |Cite
|
Sign up to set email alerts
|

Amazing grass: developmental genetics of maize domestication

Abstract: Crop plants were domesticated by prehistoric farmers through artificial selection to provide a means of feeding the human population. This article discusses the developmental genetics of crop domestication and improvement, including the historical framework and recent approaches in maize and other grasses. In many cases, selecting for a plant form that correlates with productivity involves controlling meristem activity. In the domestication of modern maize from its progenitor Zea mays ssp. parviglumis, QTL (qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 48 publications
0
13
0
1
Order By: Relevance
“…Regardless of origin, corn has proven to be one of the most adaptable crops. Its evolution apparently occurred mainly under domestication and resulted in biotypes with adaptation ranging from the tropics to the north temperate zone, from sea level to 12,000 feet altitude, and growing periods (planting to maturity) extending from 6 weeks to 13 months . Currently, the United States, Brazil, Mexico, Argentina, India, France, Indonesia, South Africa, and Italy produce 79% of the world's maize production .…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of origin, corn has proven to be one of the most adaptable crops. Its evolution apparently occurred mainly under domestication and resulted in biotypes with adaptation ranging from the tropics to the north temperate zone, from sea level to 12,000 feet altitude, and growing periods (planting to maturity) extending from 6 weeks to 13 months . Currently, the United States, Brazil, Mexico, Argentina, India, France, Indonesia, South Africa, and Italy produce 79% of the world's maize production .…”
Section: Introductionmentioning
confidence: 99%
“…huehuetenangensis) (Fig. 1B;Fukunaga et al 2005;Vollbrecht and Sigmon 2005). Genetic studies of maize domestication have identified Z. mays ssp.…”
Section: Background Informationmentioning
confidence: 99%
“…Conserving the diversity of wild relatives has become a priority for promoting food security in the face of the devastating impacts of climate change. Crop wild relatives are adapted to a diverse range of habitats and hold genetically important traits, such as biotic and abiotic stress resistance, and thus able to enhance yield and production stability (FAO, 2008;Guarino & Lobell, 2011;Maxted, Ford-Lloyd, Jury, Kell, & Scholten., 2006;Vollbrecht & Sigmon, 2005). Therefore, conserving wheat landraces is vital for the enhancement and stability of wheat production.…”
Section: Wheat Varietiesmentioning
confidence: 99%